Actividad con escritores. (UNED, 2025)
Rodrigo Arias en el podio, en la mesa principal Joaquín Calvo, Régulo Solís, Adelita Sibaja, Eugenio Rodríguez, Alberto Cañas, Luis Ferrero, Guido Miranda y Rodrigo Alberto Carazo Zeledón.